Supporting Food Security Indicator by Village Production Results Data Management for Rajaiyang Village Apparatus with Inventory Application Training - Widi Pradnyana, I Wayan; Cholil, Widya; Jayanta, Jayanta; Astriratma, Ria; Isnainiyah, Ika Nurlaili; Fosu , Agyei (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2023)
Background: Rajaiyang Village is one of the villages in Indramayu Regency which has agricultural commodities in the form of rice production. In the current condition, even though it has a fertile area, welfare data of the community is not good enough from the management of these commodity products. The village government strategy requires support of information technology and knowledge development due to support regional food security and village sustainable development goals indicators. Contribution: Increased understanding and ability to manage the availability of commodity results using information technology to support food security strategies. Method: Inducting inventory training with an internet-based inventory application system for farmer groups and village apparatus. Results: The ability of residents and village apparatus to become better, more prepared with the system and product inventory management process, together with BUMDes support as a village owned enterprise. Conclusion: Implementation strategies and supporting facilities for village food security can be improved by using updated technology, as well as collaboration between village agencies for integrated decisions